Pengaruh Dimensi-Dimensi Employee Engagement Terhadap Kinerja Pegawai Non-PNS Dinas Sosial, Pemberdayaan Perempuan Dan Perlindungan Anak Kabupaten Bantul Daerah Istimewa Yogyakarta - Purbudi Wahyuni; Tri Mardiana; Akbar Ramadhan (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2021)
This study aims to determine: (1) the effect of vigor (work spirit) on the performance of employees. (2) the effect of dedication (employee involvement) on the performance of employees. (3) the effect of absorption (enjoying work) on the performance of non-PNS employees in the Social Service & P3A of Bantul Regency. The sampling method in this study uses the saturated sampling method or the census method. Where all the population of non-PNS employee Bantul Regency Social and P3A was used as research respondents, totaling 60 people. Retrieval of data in this study using interviews and questionnaires were compiled using a Likert scale and then processed using analytical tools such as SmartPLS 3.3. The results of this study are: (1) Vigor (work spirit) has a positive and significant effect on the performance of non-civil servant employees of the Social & P3A Bantul Regency (2) Dedication (employee involvement) has a positive and significant effect on the performance of non-PNS employees in the Social Service & P3A Bantul Regency (3) Absorption (enjoying work) has a positive and significant effect on the performance of non-PNS employees in the Social Service & P3A of Bantul.